(3QSGdI aj efGbH CHj GdWjH GdeJfHjs - (3GdMGJej, eMeO Hf GdMSjf Hf GdeXaQ, J(B388(3g`s
(3ChdgG (B:s
(3GdMeO ddg hUdi Gddg Ydi SjOfG eMeOhHYO aEfj deG QCjJ eG GSJHTYg GdfGS ef YXe bOQ CHj GdWjH CMeO Hf GdMSjf GdeJfHjs
(3BNQgG (B:s
(3GQSWGWGdjS , GaQGA aQGW GdJhaj Chd ehGQO GdNha hZGjI GdeaQW aj Sdeg caGjI GdeaQW aj Mhdgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 6 / 82s
(3eYLe GdeDdajf(B: 3 / 238s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJGQjNs